THE IMPORTANCE OF BASKETBALL IN IMPROVING THE HEALTH OF UNIVERSITY STUDENTS - Mamedov Marat Raimovich; Azimova Samira (Innovate Conferences, 2025)
This article explores the role of basketball as an effective means of promoting the physical and mental well-being of university students. In the context of increasing health-related challenges among young people, regular engagement in physical activity is essential for maintaining a healthy lifestyle. Basketball, being a dynamic and accessible team sport, contributes not only to the improvement of cardiovascular and muscular systems but also enhances coordination, endurance, and psychological resilience. The article highlights the benefits of integrating basketball into university physical education programs and extracurricular activities, and discusses the motivational factors that influence students’ participation. Based on practical examples and student feedback, the study confirms the significant impact of basketball on the holistic development of youth and offers recommendations for its broader implementation in educational institutions.
Keywords: basketball, student health, physical education, university sports, youth development, physical activity, motivation